PENGARUH AMBIENT CONDITION, SPACE AND FUNCTIONALITY DAN USE OF SIGN, SYMBOLS AND ARTIFACTS TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN - Nova Yulianto, Marjam Desma Rahadhini & Sumaryanto (Universitas Slamet Riyadi, 2017)
The purpose of this study is to analyze the effect of ambient condition, space andfunctionality and sign of symbols and artifacts to consumer satisfaction and consumerloyalty. This research is a survey of Serious Coffee consumers in Solo. The sampletechnique uses accidental sampling of 100 people. Data analysis use path analysis. Theresult of the research shows that ambient condition has significant effect to customersatisfaction. Space and functionality have a significant effect on customer satisfaction.Sign of symbols and artifacts have a significant effect on customer satisfaction. Ambientcondition has a significant effect on consumer loyalty. Space and functionality have asignificant effect on consumer loyalty. Sign of symbols and artifacts have a significanteffect on consumer loyalty. Consumer satisfaction has a significant effect on consumerloyalty.Keywords: ambient condition, space and functionality, sign of symbol and artifacts,satisfaction, consumer loyalty